Strategic flexibility: How rent-seeking behavior enables firms to adapt to uncertainty - Kyriacou, Kyriacos; Liu, Siming; Mase, Bryan (Journal of Corporate Finance, 2026)
An important aspect of the conduct of business in China is the need to develop relationships and make facilitation payments in the form of entertainment and gift giving. We use three different methods to extract firms' relationship spending from their reported entertainment and travel costs, and evaluate whether this spending enhances their ability to respond and adapt to changes in the business environment – their strategic flexibility. We employ a real options approach that identifies strategic flexibility as the firm's ability to take advantage of increased uncertainty, measured as its value gain associated with increased asset volatility. We document that relationship spending is positively associated with strategic flexibility in a way that is both significant and economically meaningful, consistent with rent-seeking behavior under institutional voids. This relation is both independent of, and supplemented by, firms' political connections, and is unaffected by the important anti-corruption campaigns implemented in 2013. The relation is nonlinear, strategic flexibility declining at very high levels of spending, implying firms become over-embedded in their relationships consistent with path dependence theory. Our findings are supported by detailed robustness testing, including quasi-exogenous variation, an instrumental variable approach, a decomposition of political connectedness and the estimation of alternative specifications. Thus, we identify a new source of firms' strategic flexibility and, relatedly, an important benefit that firms derive from the associated spending. This might explain why such spending is resilient, persisting despite ongoing attempts by the government to restrict it.